PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN PADA BANK DANAMON SIMPAN PINJAM UNIT Ps. KOTA DURI - Dianita, Nana (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
The purpose of this study was to determine the effect of compensation to employee performance at Bank Danamon Simpan Pinjam Unit Ps. Kota Duri. The population in this study were all employees of Bank Danamon Simpan Pinjam Unit Ps. Kota DurI which amounted to 32 people. Sampling was conducted using a sample of saturated (Sugiyono, 2010: 96)